Thermal-hydrodynamic modeling and design for microchannel cold plates subjected to multiple heat sources - Kuiphuis, D.J.G.; Terpstra, M.J.; Wits, W.W.; Rohlfs, W. (Elsevier, 2025)
With advancing electronics, effective thermal management is crucial to maintain optimal performance and prevent overheating. Addressing the challenge of efficient cooling solutions has become a crucial area of research in modern thermal management. This paper applies and validates the Thermal-Hydrodynamic Model to bridge the knowledge gap on how straight, manifold, and serpentine microchannel configurations meet industry standards. The model predicts critical parameters, including electronic package temperatures, temperature differences across packages, thermal resistances, and pressure drops. Findings underscore the effectiveness of the model in accurately estimating thermal resistances and pressure drops within acceptable error margins compared to numerical simulations. Pressure drop estimates for straight channels consistently remain within a 10% error margin. For serpentine microchannels, the error is within 10% when the Dean number is at maximum 40. Manifold configurations, however, do not meet the 10% criterion. For manifold predictions within a 15% error margin, an Inlet Ratio of at most 0.13, a Velocity Ratio of unity, and low Reynolds numbers are necessary. Furthermore, for thermal resistance estimations, a number of grooves of at least 23 is required to maintain 10% validity. Additionally, a case study demonstrates the model’s potential as a practical alternative to simulation-based methods for identifying the optimal cold plate configuration, achieving cooling power requirements at least twice as low as other configurations within the design space.